Farming Inequality in a Changing Climate (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Climate change has become a lived reality for mountain communities in Uttarakhand, India, where temperatures are rising, rainfall is unpredictable, forest fires are common, and pest assaults are on the rise, climate change is changing the way people in mountain communities make a living. This article talks about how climate change affects marginal and small-scale farmers more than other types of farmers. It focusses on Dalit women, who are more vulnerable because of caste prejudice, gender inequality, limited property ownership, and lack of access to resources. Using examples from communities like Dhudholi and Chinoni, the article shows how disparities in opportunity for land, technological advances, sustainable crops, internet access, and government welfare programs makes it harder to adapt. State-led and non-governmental programs advocate for climate-resilient techniques, including diversification of crops, organic farming, and horticulture. However, these solutions frequently remain unattainable for the poorest farmers due to elevated costs, protracted returns, and bureaucratic obstacles. The paper contends that changing the climate in Uttarakhand is not merely an ecological emergency but also a human rights concern that jeopardises availability of food, job opportunities, and the dignity of underprivileged groups. It ends by stressing the importance of climate policies that are inclusive, take caste and gender into account, and put access, affordability, and local realities first in order to create a truly resilient cropping future.